Healthcare for migrants, participatory health research and implementation science—better health policy and practice through inclusion. The RESTORE project. (June 2014) - MacFarlane, Anne; O'Reilly-de Brún, Mary; de Brún, Tomas; Dowrick, Christopher; O'Donnell, Catherine; Mair, Frances; Spiegel, Wolfgang; van den Muijsenbergh, Maria; van Weel Baumgarten, Evelyn; Lionis, Christos; Clissmann, Ciaran; on behalf of the RESTORE consortium
Abstract Background: This is a time of unprecedented mobility across the globe. Healthcare systems need to adapt to ensure that primary care is culturally and linguistically appropriate for migrants. Evidence-based guidelines and training interventions for cultural competence and the use of professional interpreters are available across European healthcare settings. However, in real-world practice migrants and their healthcare providers 'get by' with a range of informal and inadequate strategies. RESTORE is an EU FP7 funded project, which is designed to address this translational gap. Objectives: The objective of RESTORE is to investigate and support the implementation of guidelines and training initiatives to support communication in cross-cultural consultations in selected European primary care settings. Design: RESTORE is a qualitative, participatory health project running from 2011–2015. It uses a novel combination of normalization process theory and participatory learning and action research to follow and shape the implementation journeys of relevant guidelines and training initiatives. Research teams in Ireland, England, the Netherlands, Austria and Greece are conducting similar parallel qualitative case study fieldwork, with a complementary health policy analysis led by Scotland. In each setting, key stakeholders, including migrants, are involved in participatory data generation and analysis. Expected results: RESTORE will provide knowledge about the levers and barriers to the implementation of guidelines and training initiatives in European healthcare settings and about successful, transferrable strategies to overcome identified barriers. RESTORE will elucidate the role of policy in shaping these implementation journeys; generate recommendations for European policy driving the development of culturally and linguistically appropriate healthcare systems.